2021
DOI: 10.3389/fpsyg.2021.697822
|View full text |Cite
|
Sign up to set email alerts
|

“Want to Learn” and “Can Learn”: Influence of Academic Passion on College Students' Academic Engagement

Abstract: Although research exists on the relationship between passion and engagement among employees, the mechanisms of academic passion on academic engagement among students needs to be elucidated. Guided by the broaden-and-build and situated cognition theories, we explored the positive effect of academic passion on academic engagement, the mediating effect of academic self-efficacy, and the role of teacher developmental feedback as a moderator in the relationship between academic passion and academic engagement. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
4
19
0
Order By: Relevance
“…This is owing to the indices in Table 3 which indicates that the respondents disagreed that as a consequence of post-Covid-19, they tend to distance themselves from other students, feel no enthusiasm to make frequent contributions in the classroom, be unavailable to tutor other students (paid or voluntary) during the non-school hours, feel so reluctant to discuss class issues and projects with their fellow students, focus more on the acquisition of life skills that what the teacher teaches in the class but they agreed that in the post-Covid-19 lockdown, they look out for only the subjects they enjoy most while paying less attention to others. The finding of the study agrees with Zhao, Liu and Qi [22] that academic passion has a positive relationship with academic engagement while teacher developmental feedback positively moderated the relationship between academic passion and academic engagement. Deductively, the academic passion developed by students via their teachers' efforts inspired them into engaging in their academic tasks.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is owing to the indices in Table 3 which indicates that the respondents disagreed that as a consequence of post-Covid-19, they tend to distance themselves from other students, feel no enthusiasm to make frequent contributions in the classroom, be unavailable to tutor other students (paid or voluntary) during the non-school hours, feel so reluctant to discuss class issues and projects with their fellow students, focus more on the acquisition of life skills that what the teacher teaches in the class but they agreed that in the post-Covid-19 lockdown, they look out for only the subjects they enjoy most while paying less attention to others. The finding of the study agrees with Zhao, Liu and Qi [22] that academic passion has a positive relationship with academic engagement while teacher developmental feedback positively moderated the relationship between academic passion and academic engagement. Deductively, the academic passion developed by students via their teachers' efforts inspired them into engaging in their academic tasks.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies recorded that academic passion has a positive relationship with academic engagement while teacher developmental feedback positively moderated the relationship between academic passion and academic engagement [22]. In their study, Sundaresen et al [23] observed a high anxiety level among students during the period of Covid-19 lockdown.…”
Section: Theoretical Frameworkmentioning
confidence: 86%
“…Regarding the inclusiveness of classroom practices, studies show that effective interventions are associated with a set of common characteristics, such as catering to diverse needs and expectations, proactive and flexible sessions with relevant content and well-timed instruction, collaborative and facilitated environments followed by quality feedback, and using accessible technology and media ( Thomas, 2016 ; Chiu and Hew, 2018 ; Carballo et al, 2019 ; Moriña, 2020 ; Zhao et al, 2021 ). As opposed to traditional teacher-centered instruction that prioritizes knowledge transmission through monologic lectures with limited interaction and is evaluated based on students’ ability to correctly reproduce such knowledge, inclusive pedagogy employs a constructivist approach to create an inclusive environment for all learners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies suggest that the instructor’s nurturing nature and behavior influence how students perceive their needs support ( Hinshaw and Gumus, 2013 ; Stein, 2014 ; Moriña, 2020 ). Attentive, approachable, and encouraging teachers are more likely to emotionally engage students in learning in response to their queries ( Zhao et al, 2021 ). They make reasonable adjustments to meet students’ individual needs, provide clear course requirements and expectations, and respond to student queries in a timely manner.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have indicated that school engagement has a close relation to students’ academic achievement and academic adjustment ( Lam et al, 2012 ; Chase et al, 2014 ; Galla et al, 2014 ; Stefansson et al, 2018 ; Zhu et al, 2019 ; Xiong et al, 2021 ; Zhao et al, 2021 ). Some researchers consider school engagement a predictor of the quality of education ( Reina et al, 2014 ; Li, 2018 ).…”
Section: Introductionmentioning
confidence: 99%